Review of Scaura Schwarz, 1938 (Hymenoptera: Apidae: Meliponini) - Nogueira, David Silva; Dos Santos Júnior, José Eustáquio; de Oliveira, Favízia Freitas; de Oliveira, Marcio Luiz (Zootaxa, 2019)
Scaura Schwarz is a small, widely distributed Neotropical genus of stingless bees whose workers and males have the metabasitarsus as broad as or wider than the metatibia. The genus currently includes four valid species. A species complex composed of three additional species are described here as new (S. amazonica sp. n., S. aspera sp. n. and S. cearensis sp. n.). In addition to the descriptions and redescriptions of the species of Scaura, an illustrated identification key is presented, as well as updated geographical records.